2010
DOI: 10.1002/rcm.4445
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the silver nitrate and bacterial denitrification methods for the determination of nitrogen and oxygen isotope ratios of nitrate in surface water

Abstract: Nitrogen (N) and oxygen (O) isotope ratios of NO(3) (-) are often used to trace dominant NO(3) (-) pollution sources in water. Both the silver nitrate (AgNO(3)) method and the bacterial denitrification method are frequently used analytical techniques to determine delta(15)N- and delta(18)O-NO(3) (-) in aqueous samples. The AgNO(3) method is applicable for freshwater and requires a concentration of 100-200 micromol of NO(3) (-) for isotope determination. The bacterial denitrification method is applicable for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…Furthermore, in our study, the mean corrected δ 15 N and δ 18 O values of 132 (4 KNO 3 ‐IWS per batch) The KNO 3 ‐IWS measurements in these batches were 8.4 ± 1.0‰ for δ 15 N‐NO 3 and 25.1 ± 2.0‰ for δ 18 O‐NO 3, which is 1.5‰ lower and 1.1‰ higher for δ 15 N and δ 18 O, respectively, as determined via TC/EA‐IRMS. This demonstrates the same tendency of underestimation for δ 15 N and overestimation for δ 18 O in the bacterial denitrification method as reported by Xue et al 12. The latter offsets for δ 15 N‐ and δ 18 O‐NO 3 are, however, in the range of the computed overall uncertainties for the 33 batches (0.3 to 2.2‰ for δ 15 N and 0.8 to 2.5‰ for δ 18 O).…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, in our study, the mean corrected δ 15 N and δ 18 O values of 132 (4 KNO 3 ‐IWS per batch) The KNO 3 ‐IWS measurements in these batches were 8.4 ± 1.0‰ for δ 15 N‐NO 3 and 25.1 ± 2.0‰ for δ 18 O‐NO 3, which is 1.5‰ lower and 1.1‰ higher for δ 15 N and δ 18 O, respectively, as determined via TC/EA‐IRMS. This demonstrates the same tendency of underestimation for δ 15 N and overestimation for δ 18 O in the bacterial denitrification method as reported by Xue et al 12. The latter offsets for δ 15 N‐ and δ 18 O‐NO 3 are, however, in the range of the computed overall uncertainties for the 33 batches (0.3 to 2.2‰ for δ 15 N and 0.8 to 2.5‰ for δ 18 O).…”
Section: Resultssupporting
confidence: 87%
“…Xue et al . [] compared δ 18 O‐ NO3 values in surface waters analyzed using both techniques, and concluded that the silver nitrate‐ and denitrifier‐derived results were highly correlated and generally statistically comparable. However, no precipitation samples were analyzed by Xue et al .…”
Section: Major Drivers Influencing Atmospheric Nitrate Transport In Cmentioning
confidence: 99%
“…However, no precipitation samples were analyzed by Xue et al . [] and the range of δ 18 O‐ NO3 values in their study was −19‰ to +31‰. It is unclear whether analysis of precipitation nitrate samples would show the same degree of correlation between analytical methods.…”
Section: Major Drivers Influencing Atmospheric Nitrate Transport In Cmentioning
confidence: 99%
“…However, proper correction methods with international references (USGS32, USGS34, and USGS35) are needed. As a consequence, it is important to realize that the corrected isotope values are derived from a combination of several other measurements with associated uncertainties (Casciotti et al, 2007;Chmura et al, 2009;Xue et al, 2010).…”
Section: The Atmospheric Aerosol Nitrate and The Nitrogen Cyclementioning
confidence: 99%